(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Aims: To find out the occurrence of lymph node metastasis, level of neck node involvement and the pattern of clinical presentation of patients suffering from laryngeal carcinoma. Methods: A cross-sectional study on 90 cases of laryngeal carcinoma was carried out in the inpatient department of Otolaryngology- Head and neck surgery of Dhaka Medical College Hospital, Dhaka during a period of two years. Smoking and chewing betel leaf and tobacco are the most important predisposing factors. Results: Most of the cases presented with more than one symptom. Change of voice was the commonest symptom. Cervical lymphadenopathy are significantly associated with supraglottic carcinoma. Level IV and level III is the commonest level of the lymph node involvement in laryngeal carcinoma. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 109-114